2021
DOI: 10.2147/jhc.s300633
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Metabolic Gene-Based Prognostic Signature for Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is a malignant tumor with great variation in prognosis among individuals. Changes in metabolism influence disease progression and clinical outcomes. The objective of this study was to determine the overall survival (OS) risk of HCC patients from a metabolic perspective. Patients and Methods: The model was constructed using the least absolute shrinkage and selection operator (LASSO) COX regression based on The Cancer Genome Atlas (TCGA, n=342) dataset. The Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…To further clarify the relationship between the signature and clinicopathological characteristics and prognosis in HCC patients, we performed univariate and multivariate Cox regression analysis. Univariate Cox regression analyses indicated that TNM stage (HR = 1.865, 95% CI: 1.456‐2.388) and our signature (HR = 2.794, 95% CI: 1.991‐3.920) were independent risk factors for OS in the entire TCGA cohort, similar with that of a published 10‐gene metabolic signature (Weng_ signature, HR = 3.203, 95% CI: 2.383‐4.304) 17 18 …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…To further clarify the relationship between the signature and clinicopathological characteristics and prognosis in HCC patients, we performed univariate and multivariate Cox regression analysis. Univariate Cox regression analyses indicated that TNM stage (HR = 1.865, 95% CI: 1.456‐2.388) and our signature (HR = 2.794, 95% CI: 1.991‐3.920) were independent risk factors for OS in the entire TCGA cohort, similar with that of a published 10‐gene metabolic signature (Weng_ signature, HR = 3.203, 95% CI: 2.383‐4.304) 17 18 …”
Section: Resultssupporting
confidence: 76%
“…With the swift development of high‐throughput sequencing technology, it may be conceivable to focus on systematic exploration of a class of genes associated with prediction of patient’ survival 35 . For instance, Weng, et al 17 developed a prognostic signature based on 10 metabolic genes, which reflects the metabolic and immune characteristics of tumours. Another study has identified a novel robust four‐gene metabolic signature to explain the dysregulated metabolic microenvironment and pathways 18 …”
Section: Discussionmentioning
confidence: 99%